Determinacy in new Keynesian models: A role for money after all? - Patrick Minford; Naveen Srinivasan (Cardiff University, Cardiff Business School, 2009)
The New-Keynesian Taylor-Rule model of inflation determination with no role for money is incomplete. As Cochrane (2007a) argues, it has no credible mechanism for ruling out bubbles and as a result fails to provide a reason for private agents to pick a unique stable path. We propose a way forward. Our proposal is in effect that the New-Keynesian model should be formulated with a money demand and money supply function. It should also embody a terminal condition for money supply behaviour. If an unstable path occurred the central bank would switch to a money supply Rule explicitly designed to stop it via the terminal condition. This would be therefore a threat/trigger strategy complementing the Taylor Rule - only to be invoked if inflation misbehaved. Thus we answer the criticisms levelled at the Taylor Rule that it has no credible mechanism for ruling out bubbles. However it does imply that money cannot be avoided in the new Keynesian set-up, contrary to Woodford (2008).
Keywords: E31; E52; E58; 330; New-Keynesian; Taylor Rule; Determinacy; Geldpolitik; Taylor-Regel; Geldangebot; Geldnachfrage; Inflationsrate; Bubbles; Neukeynesianische Makroökonomik; Geldtheorie